Comprehensive behavioral analysis of indoleamine 2,3‐dioxygenase knockout mice - Nao Hirata; Satoko Hattori; Hirotaka Shoji; Hiroshi Funakoshi; Tsuyoshi Miyakawa (Wiley, 2018)
Abstract Aim Indoleamine 2,3‐dioxygenase 1 (IDO1) metabolizes the essential amino acid tryptophan into kynurenine derivatives, which are involved in neural activity via the kynurenine pathway (KP). IDO1 is an initial rate‐limiting enzyme in the KP and is activated by stress and/or inflammation. The perturbation of IDO1 activity, which causes KP imbalance, is associated with psychiatric and neurological disorders. It has been reported that wild‐type (WT) mice under inflammatory conditions show increased anxiety‐like behavior and decreased novel object recognition, whereas Ido1 knockout (KO) mice do not display these behaviors. However, the behavioral phenotypes of Ido1 KO mice have not yet been fully examined under non‐inflammatory conditions. Methods We subjected Ido1 KO mice to a comprehensive behavioral test battery under normal conditions. Results Ido1 KO mice and WT mice showed similar locomotor activity, anxiety‐like behavior, social behavior, depression‐like behavior, and fear memory. In the T‐maze test, Ido1 KO mice exhibited weak but nominally significant impairment in the working memory task of the T‐maze, but this result failed to reach study‐wide significance. Conclusions Ido1 KO mice did not show any clear behavioral abnormalities under normal conditions. Further studies may be necessary to investigate their behavioral phenotype under inflammatory conditions due to their known roles in inflammation.